Steady-state analysis and experimental evaluation of a resonant AC/DC converter for HF sinusoidal AC power distribution systems - Cendoya, Marcelo Gustavo (2019)
The high frequency (HF) alternating current (AC) power distribution systems have significant advantages over their DC counterparts. This paper presents the analysis and experimental evaluation of an AC/DC resonant converter, suitable for use at the load side of HF sinusoidal AC power distribution systems. Foremost, a theoretical analysis of the converter operation in steady state and continuous conduction mode is performed. The analysis is focused on obtaining the conversion ratio, the distortion of the input current and the converter efficiency. In order to validate the theoretical analysis and to investigate the performance, a converter prototype was included in a laboratory HF sinusoidal AC distribution system. The experimental results present good correlation with predicted values obtained by means of calculations done with the mathematical expressions derived in the theoretical analysis. They also confirm the good performance of the converter for the suggested application.